Desarrollo de un proyecto de recreación dirigido a mantener la salud en el adulto mayor del hogar de ancianos del instituto Estupiñan del barrio San Sebastian de Latacunga - Santos Barahona, Nelson Guillermo (2015)
This research was conducted at the Nursing Home Estupiñan Institute of the city of Latacunga, where it was observed deficiency and lack of knowledge on physical culture and therefore does not know the benefits that involve physical activity after maintain their good health. The Elderly of "Institute Estupiñan" goes through a stage of life that is regarded as the last, in which the life projects have already been accomplished still possible to enjoy the rest of life with peace of mind. Usually elderly people in Ecuador have stopped working....